2003
DOI: 10.1242/jcs.00383
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial contact guidance on well-defined micro- and nanostructured substrates

Abstract: the native basement membrane can profoundly affect epithelial cell behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

62
862
4
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 901 publications
(932 citation statements)
references
References 51 publications
62
862
4
4
Order By: Relevance
“…Increasing feature height, while keeping constant inter-feature length, causes the space between adjacent grooves to become impervious to the cell membrane and integrins and therefore a decrease in adhesion stability occurs [70,71]. Analogous results have been observed on substrates presenting arrays of nanometric pits.…”
Section: Topo-cue-mediated Crosstalkmentioning
confidence: 60%
“…Increasing feature height, while keeping constant inter-feature length, causes the space between adjacent grooves to become impervious to the cell membrane and integrins and therefore a decrease in adhesion stability occurs [70,71]. Analogous results have been observed on substrates presenting arrays of nanometric pits.…”
Section: Topo-cue-mediated Crosstalkmentioning
confidence: 60%
“…Also, the morphology of MCF10A cells on the 400 nm line pattern showed contact guidance along the line direction presumably with more clusters of focal adhesions at the leading edges, corresponding to earlier results. 22 By contrast, MCF7 cells showed starshaped morphology (typical characteristics of cancer cell) on the 400 nm pillar and line patterns. It is noted that the elongation of MCF7 cells was not pronounced on the line pattern compared to MCF10A cells, suggesting that the adhesion of cancer cells would be relatively weak.…”
Section: Adhesions Of Mcf10a and Mcf7 Cellsmentioning
confidence: 98%
“…[19][20][21] Recently, extensive efforts have been made to understand/control cell adhesions on various surface nanostructures using conventional or unconventional lithographic techniques. [22][23][24][25] A microfluidic system is advantageous for analysis of cell adhesion in various aspects because of small sample consumption, use of multiple parameters, and generation of large shear stress. 26,27 By integrating nanostructured surfaces with a microfluidic system, we herein devise a simple, label-free cell separation and enrichment scheme based on standard soft lithography and microfluidics protocol.…”
Section: Introductionmentioning
confidence: 99%
“…However, no significant synergistic effect was observed for gravity//microgrooves. Recent reports have shown that contact guidance is closely related to three-dimensional pattern size [11,12]. Therefore, the pattern size should be optimized to weaken the unfavorable effect of gravitational field by inducing more pronounced contact guidance.…”
Section: Contact Guidance Testingmentioning
confidence: 99%